2021
DOI: 10.3389/fagro.2021.657227
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Nitrogenase Fe Protein Activity in Transplastomic Tobacco

Abstract: Integration of prokaryotic nitrogen fixation (nif) genes into the plastid genome for expression of functional nitrogenase components could render plants capable of assimilating atmospheric N2 making their crops less dependent of nitrogen fertilizers. The nitrogenase Fe protein component (NifH) has been used as proxy for expression and targeting of Nif proteins within plant and yeast cells. Here we use tobacco plants with the Azotobacter vinelandii nifH and nifM genes integrated into the plastid genome. NifH an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Regarding the functional assessment of Nif proteins expressed in yeast and plants, we have observed that many of the essential Nif components have poor solubility, especially NifH and NifB 22 , 24 , 27 , 47 . This is critical as the structural components (NifH and NifDK) are needed at very high levels during nitrogen fixation.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the functional assessment of Nif proteins expressed in yeast and plants, we have observed that many of the essential Nif components have poor solubility, especially NifH and NifB 22 , 24 , 27 , 47 . This is critical as the structural components (NifH and NifDK) are needed at very high levels during nitrogen fixation.…”
Section: Discussionmentioning
confidence: 99%
“…3 ). To minimize O 2 exposure produced during photosynthesis and maximize the isolation of functional Os NifH Ht , plants were Fe-fertilized and harvested before onset of light at the end of the dark period, following a procedure previously shown to be successful to obtain active NifH Av and NifH Ht from tobacco chloroplasts and mitochondria 15 , 23 . Purified Os NifH Ht was mostly soluble and could be isolated from plant line Ht200 with yields of 0.5 mg kg −1 fresh weight (1-month-old plants) or 0.25 mg kg −1 fresh weight (2-month-old plants).…”
Section: Resultsmentioning
confidence: 99%
“…The heat treatment precipitated apo-NifH protein lacking [4Fe-4S] clusters, and therefore enriched the holo-protein, increasing the specific activity of the remaining NifH protein. The study suggested that the endogenous [Fe-S] cluster biosynthesis system in plastids was, like that in N. benthamiana mitochondria, insufficient for complete NifH maturation 23 . Similar results were reported by the transient expression of soluble A. vinelandii NifH, NifM, NifU and NifS in N. benthamiana chloroplasts 14 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation